Changes in some biochemical blood parameters of quails (Coturnix coturnix japonica) with increasing stocking density - Erisir, M; Erisir, Z (Scientific Technical Research Council Turkey, 2002)
Effects of population density on the biochemical blood parameters of Japanese quails were investigated according to sex, Female and male quails were separated into three groups in 360 cm(2) cages and groups I, II and III consisted of 2,3 and 4 quails respectively. In male quails, with increasing stocking density, serum glucose, inorganic phosphate and calcium levels increased (P<0.001 and P<0.05), whereas serum creatinine and uric acid levels decreased significantly (P<0.01 and P<0.001). No statistically significant differences were found in ALP and total protein levels among the groups. In female quails, while no significant differences were found in Ca, Pi, ALP, creatinine and total protein levels with increasing stocking density, glucose and uric acid levels increased significantly (P<0.001). There were differences between the responses of male and female quails to stocking density. As a result of increased stocking density, quails' immune defenses may be decreased, thus leading to increased susceptibility to infections.
Yerleşim sikli?i arttirilan bildircinlarin (Coturnix coturnix japonica) bazi biyokimyasal kan parametrelerindeki de?işiklikler
Keywords: stocking density; biochemical blood parameters; quail